Adaptive Fractional Differentiation Harris Corner Detection Algorithm for Vision Measurement of Surface Roughness. (17th April 2014) - Tang, Rui-Yin; Zeng, Zhou-Mo
Abstract : The Harris algorithm via fractional order derivative (the adaptive fractional differentiation Harris corner detection algorithm), which adaptively adjusts the fractal dimension parameter, has been investigated for an analysis of image processing relevant to surface roughness by vision measurements. The comparative experiments indicate that the algorithm allows the edge information in the high frequency areas to be enhanced, thus overcoming shortcomings. The algorithm permits real-time measurements of surface roughness to be performed with high precision, superior to the conventional Harris algorithm.